Smartphone Applications for Assessing Ankle Range of Motion in Clinical Practice. Issue 3 (17th September 2019) - Wang, Kevin Y.; Hussaini, S. Hanif; Teasdall, Robert D.; Gwam, Chukwuweike U.; Scott, Aaron T.
Background: Measuring ankle range of motion (ROM) following injury or intervention is necessary for monitoring recovery as well as for calculating permanent impairment ratings in workers' compensation cases. In recent years, smartphone application developers have created applications (apps) that emulate ROM measurement tools like the universal goniometer. This study assessed the correlation between smartphone ROM measurements and universal goniometer measurements, as well as the reliability and usability of these apps in clinical practice. Methods: Three raters used the Goniometer app (Gonio), Clinometer app (Clino), DrGoniometer app (DrG), and a universal goniometer (UG) to assess the ankle ROM in plantarflexion and dorsiflexion of 24 patients with ankle pathology. Each patient completed a survey on the usability of the apps. Results: Lin's concordance correlation coefficient test showed moderate correlation between the smartphone and UG measurements (Lin's correlation coefficient [rLC] = 0.931, 95% confidence interval [CI] = 0.911-0.946 for UG-Gonio; rLC = 0.908, 95% CI = 0.881-0.929 for UG-Clino; rLC = 0.935, 95% CI = 0.915-0.950 for UG-DrG). A 2-way mixed model showed good to excellent interrater reliability for each app for plantarflexion and dorsiflexion (ICCp = 0.836, ICCd = 0.912, P < .001 for Gonio; ICCp = 0.788, ICCd = 0.893, P < .001 for Clino; ICCp = 0.777, ICCd = 0.897, P < .001 for DrG). Most participants surveyed were very comfortable with having their ankle ROM measured by a smartphone. Conclusion: Smartphone apps may be a more convenient way to measure ankle ROM than UG. Physicians can use these apps to measure a patient's ROM in clinic, a patient could send a picture of his or her dorsiflexed or plantarflexed ankle to the physician to remotely track ROM, or a patient could measure his or her own ROM at home using a personal smartphone. Level of Evidence: Level IV, case series.